(3JdNjU cJGH LGdjfhS aj MjdI GdHQAs - (3CHh HcQ eMeO Hf RcQjG GdQGRis ((3ZQfGWI s)
(3ChdgG (B:s
(3Led GdebGdI GdChdi , hgj CQHYI aUhd , GdChd GdcdGe ai UOQ gPG GdcJGH s
(3BNQgG (B:s
(3adjced gGgfG cJGHfG HGSJjaGA LejY eG hYOfG Hg , hdhGgH GdYbd GdMeO HdG fgGjI , ceG gh Cgdg heSJMbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
GALS - (3GdLRA (B3 - (3U (B291 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B68 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda (B: (3YdjgG ebGHdI Ydi GdfSNI GdCes
Keywords: (3GdWHs